Targeting VCAM-1 with chimeric antigen receptor and regulatory T cell for abdominal aortic aneurysm treatment - Gang, Qingwei; Lun, Yu; Zhang, Xiaoxu; Uzokov, Jamol; Jiang, Han; He, Yuchen; Shen, Shikai; Wang, Shiyue; Erhart, Philipp; Böckler, Dittmar; Li, Yuemeng; Han, Yanshuo; et al. (Communications biology, 2025)
Abdominal aortic aneurysm (AAA) is a life-threatening condition characterized by the dilation of the abdominal aorta, leading to a high risk of rupture. Current treatment options are limited, particularly for patients ineligible for surgical interventions. This study explores a novel immunotherapeutic approach using chimeric antigen receptor Treg cells targeting vascular cell adhesion molecule-1 (VCAM-1) to mitigate AAA progression. By leveraging the specificity and regulatory function of CAR-Treg cells, our research aims to modulate the immune response and reduce inflammation in the aneurysmal wall. Results from preclinical mouse models demonstrated that CAR-Treg cells effectively homed to the aneurysmal site, suppressed local inflammation, and decreased aortic dilation compared to control groups. These findings suggest that CAR-Treg cell therapy could provide a promising, non-surgical treatment option for AAA patients, addressing a critical unmet need in cardiovascular disease management.
Veröffentlicht: 15. August 2025
Gesehen am 13.01.2026